Vplyv chinidínu na plazmaticků hladinu digoxínu po vynechání digoxínovej liečby - Markuljak, Imrich; Květenský, Josef; Ličko, Vladimír; Dvorský, Ján; Funiak, Stanislav; Záhradný, V (Vnitřní lékařství, 1990)
The authors submit a report on the effect of quinidine on plasma digoxin. The investigation was made in 20 patients wit supraventricular dysrhythmia. After initial digoxin treatment they proceeded with quinidine six hours after the last digoxin dose. Although they did not administer digoxin, the digoxin level increased during quinidine treatment in the course of 12 hours from 2.4 +/- 1.6 ng/ml to 3.8 +/- 12.4 ng/ml. The authors draw attention to the importance of following up digoxin levels in the mentioned drug combination which is supposed to prevent serious complication caused by possible digoxin intoxication.
Keywords: digoxin; ženské pohlaví; lidé středního věku; lidé; Female; mužské pohlaví; chinidin; Male; Digoxin; lékové interakce; Middle Aged; Drug Interactions; srdeční arytmie; Quinidine; Arrhythmias, Cardiac; Humans